Slippy snail (Cottage farm, England igloo books, 2018)
Join Slippy snail and his mummy in a game of hide-and-seek, with charming illustrations and a soft finger puppet, this is a wonderfully fun and interactive book for babies
English stories
1
Keywords: English stories